Antiphospholipid and Antiprotein Syndromes in Non-thrombotic, Non-autoimmune Women with Unexplained Recurrent Primary Early Foetal Loss - Gris, Jean-Christophe; Quéré, Isabelle; Sanmarco, Marielle; Boutiere, Brigitte; Mercier, Eric; Amiral, Jean; Hubert, Anne-Michèle; Ripart-Neveu, Sylvie; Hoffet, Méderic; Tailland, Marie-Laure; Rousseau, Olivier; Monpeyroux, Françoise; Dauzat, Michel; Sampol, José; Daures, Jean-Pierre; Berlan, Jacques; Marès, Pierre (Thrombosis and Haemostasis, 2000)
Various antiphospholipid and/or antiprotein antibodies have been suspected to be associated with recurrent early foetal loss in absence of any habitual aetiology. We conducted a hospital-based case control study on women with no antecedent of thromboembolic or autoimmune disease. We studied 3 groups of 518 women: patients with unexplained primary recurrent early foetal loss, patients with explained episodes and mothers with no previous obstetrical accident. Matching the 3 groups was carried out on the basis of age, number or pregnancies and time elapsed since the end of the last pregnancy. Significant biological markers were then prospectively tested.The various antibodies were shown to be dependent on parity and on the presence of previous foetal loss: cut-off values were thus calculated using data obtained from the group of explained accidents, and adjusted for parity. Only anti-phosphatidylethanolamine IgM [odds ratio: 6.0, 95% confidence interval (2.3–15.7), p = 0.0003], anti-β2-glycoprotein I IgG [4.4, (1.6–11.7), p = 0.0035] anti-annexin V IgG antibodies [3.2 (1.2–8.1), p = 0.015] and lupus anticoagulant [3.0, (1.3–6.8), p = 0.009], were found to be independent retrospective risk factors for unexplained early foetal loss. These four markers were subsequently found to be, during the following pregnancy, associated with a significant risk of foetal loss despite a low-dose aspirin treatment.In non-thrombotic, non-auto-immune women with unexplained primary reccurent early foetal loss, subgroups of patients with positive anti-phosphatidylethanolamine IgM antibodies, or positive anti- β2-glycoprotein-I IgG antibodies, or positive anti-annexin V IgG anti-bodies or lupus anticoagulant must be particularised. This should allow therapeutic trials to be carried in well-defined patients.
Keywords: Foetal loss; antiphospholipid antibodies; β2 glycoprotein I; annexin V; phosphatidylethanolamine